Molecular HLA typing for bone marrow transplantation in Malaysia - Yih, P.T.; Phipps, M.E.; Bosco, J.J. (Malaysian Society for Molecular Biology and Biotechnology, 1999)
In recent years, there have been various advancements in HLA typing for transplantation. Molecular methods such as restriction fragment length polymorphism (RFLP), PCR SSO, and PCR SSP have been developed to supplement and even replace conventional serological. typing methods for transplantation especially bone marrow transplantation. HLA typing at the molecular level permits a resolution that is higher without the problems associated with serological cross reactivity. Furthermore, new alleles are constantly being elucidated. We have modified and utilized a comprehensive molecular typing method known as Phototyping. It is based on sequence specific primer amplification (PCR SSP) and was initially developed at the Oxford Transplant Centre in 1995. We phototyped 30 individuals involved in the University Malaya Medical Centre (UMMC) Bone Marrow Transplantation progamme for HLA A, B, DRB1, DRB3, DRB4, DRB5 and DQBI at the medical faculty and compared the results blind with HLA typing (DNA typing) done at the CMII (Centre for Molecular Immunology and Instrumentation, University of Western Australia) on the same individuals. Upon comparison of results, we report that the overall concordance is excellent for all matched loci except for some minor discrepancies at HLA B loci. Although our method requires a high degree technical of expertise, it is reliable and reproducible. This study demonstrates the feasibility of molecular HLA typing in the Malaysian transplantation scenario.